Rubik’s Snake Simulator For PC - Rikip Ginanjar; Natasha Janice (President University, 2018)
Rubik’s Snake is a toy that can be played by people with almost all ages. It is usually formed of 24 edges of right isosceles triangular prisms that are connected with spring bolts so that each edges can be rotated in some way to form a shape. Rubik’s Snake is a tool to test an idea of shape in space. This research will develop a 3D Rubik’s Snake simulator for PC with “Snix” as the name of the application. The simulator is expected to imitate a real Rubik’s Snake behavior that its edge can be rotated in some way to form shapes by implementing existing 3D computer graphics algorithms